Benign Metastasizing Leiomyomatosis to the Skin and Lungs, Intravenous Leiomyomatosis, and Leiomyomatosis Peritonealis Disseminata: A Series of Five Cases. (28th January 2022) - Boavida Ferreira, João; Cabrera, Rafael; Santos, Filipa; Relva, Andreia; Vasques, Hugo; Gomes, António; Guimarães, António; Moreira, António
Abstract: Benign metastasizing leiomyomatosis (BML) is a rare disease that typically occurs in women with a history of uterine leiomyomatosis. Benign metastasizing leiomyomatosis occurs more frequently in the lungs but may also develop in other organs and tissues. Other unusual variants of extra-uterine leiomyomatosis include intravenous leiomyomatosis (IVL) and leiomyomatosis peritonealis disseminata (LPD). In this article, three cases of BML are presented. One case, in a premenopausal woman, presented cutaneous metastases. We also present a case of IVL and a case of LPD, which occurred in postmenopausal women. Given the rarity of BML, IVL, and LPD, the authors reviewed the literature and herein discuss the implications for treatment in all five cases. Evidence for treating BML, IVL, and LPD is still scarce, and data available from our series and other small series seem to point to the patient's hormonal status playing a fundamental part in the treatment plan. Furthermore, a collecting bag when performing excision of uterine leiomyomas may help avoid the potential spreading of leiomyomatosis. Hysterectomized patients with chronic cough, frequent respiratory infections, abdominal discomfort, right heart failure, or non-specific symptoms should be actively screened for BML, IVL, and LPD. Treatment should be individualized according to each patient's hormonal status and desires.